QUANTITATIVE ASSESSMENT OF HEAVY METALS IN COAL-FIRED POWER PLANT’S WASTE WATER - Haneef, Fahad; Akıntuğ, Bertuğ (MATTER: International Journal of Science and Technology, 2016)
Coal-fired power plants are water intensive sources of energy generation. Waste water dumped by these coal-fired power plants is significant threat to our environment and human health. The electric power sector is the major source of toxic wastes in Pakistan, due to coal ash and coal waste, which contain toxic heavy metals such as Cr, Co, Cu, Pb, Mn, Ni, Zn, Hg, Ag, and As. Different Environmental report shows nearly all power plants in Pakistan discharge toxic coal ash or wastewater into public water. This paper provides a brief overview about how badly Coal Industry is poisoning water and later on the characteristics of wastewater discharge from coal based thermal plants are discussed. The study presented in this paper quantitavely evaluates the heavy metals like Cr, Ni, Hg, As, Cd, Pb, Mn and Co emissions in coal ash or waste water of a coal power plant. 1 MW capacity plant was selected for the study and the results showed such a plant will produce Cr 33.7g/kWh, Pb 44.9g/kWh, As 44.9g/kWh and Hg 0.6g/kWh respectively. At the end, some plausible recommendations are suggested for government of Pakistan to mitigate the effects of these power plants.